Conspiracy thinking, conspiracy beliefs, denialism, motivation, and COVID-19 vaccination intentions in Costa Rica - Reyes Fernández, Benjamín (2024)
An observational cross-sectional study was conducted among inhabitants of Costa Rica to examine motivational determinants of COVID-19 vaccination intentions (CVI), as well as to better understand the role of a set of conspiracy-related variables within the framework of the Theory of Planned Behavior (TPB). Data were collected online, and a subsample of those not yet vaccinated (N = 406, age = 44.35, S. D. = 13.23, 74.9% women) was selected. They reported TPB-variables, risk perception, conspiracy-related variables, and sociodemographic information. Structural equation was used to model the assumption that conspiracy beliefs presented direct and indirect effects on intentions. Conspiracy thinking, denialism, and sociodemographic information were also specified as determinants of conspiracy beliefs and vaccination intentions. Most determinants presented direct effects on intentions. Only perceived behavioral control, denialism, and conspiracy thinking presented no direct effects on intentions. Conspiracy beliefs had indirect effects on intentions via most TPB-variables and risk perception. Conspiracy beliefs were predicted only by conspiracy thinking, gender (male), and education. Sociodemographic variables had no effects on intentions. Evidence suggested that a mechanism integrating conspiracy-related variables, risk perception, and TPB-variables predicted CVI. Education and gender played a role in the onset of conspiracy beliefs and thereafter vaccination intentions.